Facebook: can it be a diagnostic tool for neurologists?. (22nd August 2012) - Mittal, Manoj K; Sloan, Jeff A; Rabinstein, Alejandro A
Abstract : A 56-year-old woman presented with acute ischaemic stroke with NIHSS 13. She had right eye ptosis and miosis. She and her husband were not sure if her facial features were different than usual. With her consent, we compared her face with her pictures on Facebook. In the absence of any ptosis or miosis in her pictures, she was diagnosed with acute Horner syndrome. Facebook may be a useful tool for the neurologists to define the timing of facial neurological signs.